Molecular phylogeny of the Chinese weedy rice based on nrDNA ITS and two cpDNA sequences - Zhiwen, Liu; Shiqi, Zhang; Dong, Zhai; Fang, Yu; Zhaoxia, Jin; Wenfu, Chen (The Indian Journal of Genetics and Plant Breeding, 2016)
Direct sequencing data from the nuclear ribosomal DNA internal transcribed spacer (nrDNA ITS) region and two chloroplast DNA (cpDNA) fragments (psbA-trnH and petGtrnP) of Chinese weedy rice (Oryza stavia L. f. sp. spontanea) were analyzed separately and simultaneously in the MEGA 6.0 software. The nrDNA, cpDNA and cpDNA+nrDNA phylogenetic trees showed that the weedy rice collected from Northern China, Oryza sativa Japonica group and Oryza rufipogon, were on the one phylogenic node whereas weedy rice were collected from Southern China and Oryza sativa Indica group were on the other phylogenic node. The results revealed that there were geographical and indica-japonica differentiations in Chinese weedy rice which were corresponding to their geographical distribution and cultivated rice (Oryza sativa) indica-japonica differentiation. These results demonstrated that Chinese weedy rice from different regions have diverse origins and they were the relative origin group of the cultivated rice as there is no wild form available in Northern China. Additionally, clone sequence variation of the nrDNA ITS regions in intraindividual weedy rice provides evidence origin of other Oryza taxa through the process of hybridization or introgression. Data from this research further confirmed that the Chinese weedy rice was evolved from local rice varieties (as the female parent) which naturally hybridized with other oryza materials.